2006
DOI: 10.1016/j.jacc.2006.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Noncontact Mapping System in the Left Atrium During Permanent Atrial Fibrillation and Sinus Rhythm

Abstract: Noncontact mapping can be performed in human LA; however, the accuracy of reconstructed electrograms is poor >40 mm from the center of the array, particularly during AF. Care must be taken interpreting isopotential maps if the entire endocardial surface of the LA is not close to the array.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 15 publications
8
78
0
Order By: Relevance
“…It was also shown that correlation decreased with increasing distance between the endocardial node and the balloon [40,42]. However, these comparisons were limited on the correlation of the morphology of electrograms.…”
Section: Estimating Df Using Ncmmentioning
confidence: 99%
“…It was also shown that correlation decreased with increasing distance between the endocardial node and the balloon [40,42]. However, these comparisons were limited on the correlation of the morphology of electrograms.…”
Section: Estimating Df Using Ncmmentioning
confidence: 99%
“…6,7,8 Our report demonstrates its utility and safety in the management of multiple cardiac arrhythmias, often leading to successful ablation after previous failure using other techniques. A variety of catheter and energy types were used including cryoablation and low energy DC.…”
Section: Discussionmentioning
confidence: 78%
“…7,10,11 Consequently, when mapping in large cardiac chambers it is important to position the equator of the MEA as close as possible to the area of interest-this may require conventional mapping before deploying the balloon, or repositioning and remapping.…”
Section: Specific Technical Pointsmentioning
confidence: 99%
“…The noncontact array balloon with 64 electrodes was placed in the left atrium transeptally, and electrograms were collected using inverse solution mathematics and interpolation in an inside-out fashion allowing the reconstruction of up to 3,600 simultaneous unipolar AEGs projected to the atrium's anatomical 3D representation 3D geometry of the atrium performed at the beginning of the EP procedure. The array was not moved after geometry creation to avoid distortion of the isopotential maps [12][13][14][15][16][17] and the distance between the centre of the balloon and the patient's endocardium wall did not exceed 4 cm (checked with fluoroscopy).…”
Section: Study Populationmentioning
confidence: 99%